The music of Herbert Howells - Cooke, Phillip A.; Maw, David Nicholas (Boydell & Brewer, 2013)
Herbert Howells (1892-1983) was a prodigiously gifted musician and the favourite student of the notoriously hard-to-please Sir Charles Villiers Stanford. Throughout his long life, he was one of the country's most prominent composers, writing extensively in all genres except the symphony and opera. Yet today he is known mostly for his church music, and there is as yet relatively little serious study of his work. This book is the first large-scale study of Howells's music, affording both detailed consideration of individual works and a broad survey of general characteristics and issues. Its coverage is wide-ranging, addressing all aspects of the composer's prolific output and probing many of the issues that it raises.